Analisis Model Perilaku Konsumen Dan Proses Pengambilan Keputusan Dalam Manajemen Pemasaran Perspektif Ekonomi Syariah - Tito, Luki; Fauzan Mutakin, Agil; Fuji Amalia, Bunga (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2025)
This study aims to analyze consumer behavior models and decision-making processes from the perspective of Islamic economics and their application in marketing management. Using a literature review method, this research examines relevant literature on key concepts in consumer behavior and the underlying principles of Islamic economics. In Islamic economics, consumer behavior is not solely based on economic rationality but is also guided by ethical and moral values in Islam, such as justice, honesty, and balance. The decision-making process in this perspective considers aspects of halal and haram, sustainability, and the social impact of the decisions made. The study finds that applying Islamic economic principles in marketing management can enhance consumer trust and loyalty toward marketed products or services. Thus, a deep understanding of consumer behavior within the scope of Islamic economics offers a strong opportunity to implement effective marketing management in line with Sharia principles.. Keywords: Consumer Behavior, Islamic Economics, Decision-Making, Marketing Management, Consumer Loyalty